Firm Location, Transport Connectivity, and Agglomeration Economies Evidence from Liberia - Iimi, Atsushi (The World Bank, 2018)
Transport connectivity is among the most important factors in increasing firm productivity and accelerating economic development. The literature generally supports the idea of agglomeration economies, although there is little evidence of their effectiveness in Africa. There are often empirical challenges, such as spatial externalities and endogeneity of infrastructure development. Using firm registry data in Liberia, this study used the instrumental variable spatial autoregressive model to examine the effects of transport connectivity on firms' decisions on where to locate. The study found significant spatial autocorrelation and possible endogeneity related to transport infrastructure, and that firms are more likely to be located where market accessibility is better. The data indicated strong agglomeration economies, indicating that the primary city, Monrovia, is likely to continue to grow and attract more people and firms, and that secondary cities can also grow with greater transport connectivity between populated areas, such as district centers